Physicochemical characteristics of three accessions of sweet potato cultivated by traditional growers of Vale do Ribeira, Sao Paulo State, Brazil - Mendoza, J.; Vargas, P. [UNESP]; Evangelista, M.; Sartori, M.; Ming, L. C. (International Society for Horticultural Science (ISHS), 2018)
The sweet potato is one of the major vegetable crops grown in the world; its storage roots have multiple uses as food and feed and in the industrial production of flour, starch and ethanol. The starch and sugar contents may differ between genotypes and harvest seasons. The Vale do Ribeira region has traditional communities, wherein different accessions of sweet potato are cultivated. This study was conducted from February to October 2015, and the main objective was the chemical characterization of three accessions of sweet potato belonging to the Germplasm Bank of Universidade Estadual Paulista. Accessions used include VR 13-01 (purple skin and strongly purple pulp), VR 13-11 (lightly purple skin and cream pulp) and VR 13-50 (white cream skin and pulp). The experimental design was randomized blocks with six replicates per treatment and each plot had 5 plants. The spacing between plants was 0.25 m, and 0.80 m between rows. The physicochemical characterization was made 150 days after planting. The total soluble solids (TSS) as well as the reducing sugar and starch contents were determined and significant differences among accessions were obtained by ANOVA, with means separated by Tukey test. Comparing all three accessions, VR 13-01 showed the highest TSS (15.1 °Brix) and the accession VR 13-50 showed the highest starch content (19.1%) and the highest level of reducing sugars (0.64%). These results have showed that accessions VR 13-01 and VR 13-50 can be used for breeding programs as plant materials with superior characteristics and both in the industrial production and as vegetable crops.
Keywords: Ipomoea batatas L.; Physicochemical characteristics; Starch; Sugar